PENGARUH KEPEMIMPINAN AUTENTIK PADA KINERJA GURU SMA NEGERI 1 BULUKUMBA - , Andi Nasrum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine and analyze the effect of the dimensions of selfawareness, dimensions of relational transparency, dimensions of balanced processing, and dimensions internalized moral perspective on teachersâ performance. The instrument used to measure teachersâ performance refers to the model of items developed by Stronge (2006) and authentic leadership model items used by Walumbwa et.al., (2008). To answer the research questions used questionnaires. Methods of data collection techniques used was sample census technique, which all high school teachers of Bulukumba State 1 well with the status of civil servants as well as part-time teachers. This study uses multiple linear regression analysis with the aim of answering the effect of authentic leadership on teachersâ performance. The results showed that (1) the dimensions of self-awareness and a significant positive effect on teacher performance (Î²=0.256